Strategi Komunikasi Publik Gugus Tugas Covid-19 (Studi Komunikasi Publik Pada Program Larangan Mudik Lebaran Tahun 2021) - Banyugiri Setra; Abul Razaq; Miftahul Arifin (Jurnal Al-Hikmah, 2021)
Indonesia and the world are being hit by the global Covid-19 pandemic which has paralyzed all human activities for several months. The incident then seizes public's attention and becomes the centre of public discussion. Various state policies around the world have been carried out to prevent the spread of Covid-19, including social distancing, Large-Scale Social Restrictions, and the implementation of the ‘new normal’ in various sectors. In this case, the current article specifically focuses on the issue of the mudik (exodus) restriction which has caught the attention of Indonesian public. Such travel restriction has caused a polemic between the government and migrants or migrant workers. These problems became complex when the mudik restrictions were started earlier on May 6, 2021. Despite the restrictions, the euphoria of the public in welcoming the Idul Fitri could no longer be contained although the complexity of the country in implementing this policy was still a problem, whether mudik was allowed or prohibited. Such perception was a polemic in our society. Therefore, the purpose of this journal article is to shed some of the answers to the many question posed in public perception. It is also used to provide more space and access to the public in understanding the ambiguity of the rules.